Study on the Nutritional Composition of Oil Cakes of Different Released and Line Cultivars of Mustard and Rapeseed (Brassica spp.) - Islam, S.; Shelly, N. J.; Ahmed, K. U.; Chowdhury, S. R. (International Journal of Bio-resource and Stress Management, 2020)
An experiment was conducted to study the nutritional composition of oil cakes of four released and two line cultivars of mustard and rapeseed (Brassica spp.). SAU Sarisha-2 had the highest amount of oil cake (61.26%) while BARI Sarisha-9 contained lowest amount of oil cake (59.45%). The highest dry weights of cake (56.56%), ash content (14.00%) and protein content (28.05%) was obtained from SAU Sarisha-2 and the lowest value obtained from BARI sarisha-9 which was (54.68%), (11.00%) and (25.05%) respectively. The highest amount of carbohydrate was found in Tori-7 (19.08%) and it was lowest in SAU Sarisha-2 (14.51%). Calcium and Magnesium content ranged from 0.722% to 1.006% and 0.370% to 0.838% respectively. Significantly highest amount of calcium (Ca), Magnesium (Mg) and Iron (Fe) was observed in Tori-7 (1.006%), (0.838%) and (101.3 ppm) respectively while the lowest amount of Ca (0.722%) from SAU sarisha-2 and lowest Mg (0.370%) and Fe (30.0 ppm) was obtained from BARI Sarisha-9. Copper and Zinc content ranged from 1.205 to 3.955 ppm and 24.30 to 51.12 ppm respectively. Cu and Zn content was highest in Tori-7×BARI Sarisha-6 (3.955 ppm) and (51.12 ppm) respectively while they are lowest in SAU Sarisha-2 (1.205 ppm) and (24.30 ppm) respectively. Gross energy ranged from 518.9 to 540.3 kcal g-1 and it was highest in BARI Sarisha-9 (540.3 kcal g-1) and lowest in SAU Sarisha-2 (518.9 kcal g-1).